Two cases of pseudohyperkalemia that occurred after emergency splenectomy, what goes up, will come down - Tan GH,; Nor Faezan AR,; Hairol AO,; Bong JJ, (Department of Surgery, UKM Medical Centre, 2011)
Pseudohyperkalemia is a spuriously high serum potassium measurement in a patient with no clinical evidence of hyperkalemia. It has been reported to occur in patients with leukocytosis and thrombocytosis. Only a few cases of pseudohyperkalemia have been reported in patients after splenectomy. Two cases of pseudohyperkalemia occurring after emergency splenectomy for abdominal trauma are presented to highlight their clinical presentation and sequalae. Consecutive patients who underwent emergency splenectomy for trauma and subsequently developed pseudohyperkalemia were monitored in Universiti Kebangsaan Malaysia Medical Centre for their clinical sequalae. Both the patients developed leukocytosis, thrombocytosis and high serum potassium level within 2-weeks of their splenectomies. They did not demonstrate any symptoms and signs of hyperkalemia. Their conditions resolved spontaneously without any specific treatment. Pseudohyperkalemia should be suspected in a similar clinical scenario to avoid unnecessary treatment that could lead to severe hypokalemia.